2012
DOI: 10.1177/0022146512444289
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Forms of Perceived Discrimination and Health among Adolescents and Young Adults

Abstract: Research on perceived discrimination has overwhelmingly focused on one form of discrimination, especially race discrimination, in isolation from other forms. The present article uses data from the Black Youth Culture Survey, a nationally representative, racially and ethnically diverse sample of 1,052 adolescents and young adults to investigate the prevalence, distribution, and mental and physical health consequences of multiple forms of perceived discrimination. The findings suggest that disadvantaged groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
245
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(260 citation statements)
references
References 55 publications
12
245
3
Order By: Relevance
“…We also see consistent patterns suggesting Black adults with diabetes have compounded disadvantages noted in other populations managing both racial minority status and health-related experiences [11]. When we factor in literatures concerning Black female bodies, sexuality, and health [12,13], for example, these patterns appear quite striking, and suggest there may be much to learn from systematic examinations of the experiences of Black people -and especially Black cis and trans women -managing diabetes, sexualities, and bodily appearance.…”
Section: Discussion Key Findingssupporting
confidence: 69%
“…We also see consistent patterns suggesting Black adults with diabetes have compounded disadvantages noted in other populations managing both racial minority status and health-related experiences [11]. When we factor in literatures concerning Black female bodies, sexuality, and health [12,13], for example, these patterns appear quite striking, and suggest there may be much to learn from systematic examinations of the experiences of Black people -and especially Black cis and trans women -managing diabetes, sexualities, and bodily appearance.…”
Section: Discussion Key Findingssupporting
confidence: 69%
“…Social capital may provide the motivation, by means of obligation, reciprocity and self-control, to invest in future family health. There is a vast literature suggesting that experiencing different types of personal or institutional discrimination has detrimental effects on health, including nutritional risk (30,31) . In the present study it was revealed that intolerance of diversity had negative associations with the Mediterranean diet score and thus the healthy dietary patterns of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…To further map the prevalence of chronic conditions within and between such populations, we then asked a core question in intersectional studies of health (Grollman 2012): how do chronic physical condition frequencies vary in relation to intersecting social locations among nonreligious people? We defined "chronic conditions" as any diagnosed health condition capable of producing consistent and recurrent symptoms.…”
Section: Research Questionsmentioning
confidence: 99%
“…Such efforts follow the insights of intersectional scholars by critically examining the concrete experiences of people in varied social locations instead of expecting specific relationships a priori or simply repeating dominant cultural discourses (i.e., religion is good, see Barton 2012) that say more about societal power relations than actual health experience (see Grollman 2012;Schultz & Mullins 2006 for examples). This process should begin with assessment of baseline variation in health status between and within populations, and proceed to exploration of the ways in which health may be influenced by intersecting social locations.…”
mentioning
confidence: 99%
See 1 more Smart Citation